The effect of terrorist incidents on capital flows - Randall Filer; Dragana Stanišić (Center for Economic Studies and ifo Institute (CESifo), 2012)
Current literature shows a significant negative impact of terrorism on countries economies. We explore this relationship in more detail. Using an unbalanced panel of over 160 countries for up to 25 years and the Global Terrorism Database (GTD) we show a decrease in FDI as a consequence of terrorism. We also find evidence that FDI flows are more sensitive to terrorism than either portfolio investments or external debt flows. Finally, we test the hypothesis that terrorism has negative spill-over effects on FDI flows into neighboring countries and find evidence that cultural but not geographical closeness matters.
Keywords: F20; 330; FDI; terrorism; lending; portfolio investment